2015
DOI: 10.2169/internalmedicine.54.3917
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carcinoma with Bone Marrow Metastasis: Positive Response to Weekly Paclitaxel Chemotherapy

Abstract: A 51-year-old man with nasopharyngeal carcinoma underwent chemoradiotherapy with cisplatin and 5-fluorouracil, followed by a left cervical lymphadenectomy. Distant metastatic disease was excluded using fluoro-deoxyglucose positron emission tomography. Seven months later, bone marrow metastasis and disseminated intravascular coagulation were diagnosed. The patient received weekly paclitaxel therapy and maintained a good performance status for seven months. During the treatment period, the patient developed no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Paclitaxel is an anti-cancer chemotherapeutic that stabilizes polymerized microtubules in metaphase, preventing the progression to anaphase in rapidly dividing cells (Schiff and Horwitz, 1980; Risinger et al ., 2014). It is one of the most commonly administered and effective chemotherapeutics in the United States and throughout the world, and it has been used to improve survival in patients with nasopharyngeal (Miyaushiro et al ., 2015), non-small cell lung (Langer et al ., 2015), breast (Sparano et al ., 2008), and ovarian cancers (Suh et al ., 2013). Clinical use of paclitaxel is limited by adverse effects that include emesis, alopecia, and diarrhea, but these effects typically resolve with cessation of treatment (Reeves et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is an anti-cancer chemotherapeutic that stabilizes polymerized microtubules in metaphase, preventing the progression to anaphase in rapidly dividing cells (Schiff and Horwitz, 1980; Risinger et al ., 2014). It is one of the most commonly administered and effective chemotherapeutics in the United States and throughout the world, and it has been used to improve survival in patients with nasopharyngeal (Miyaushiro et al ., 2015), non-small cell lung (Langer et al ., 2015), breast (Sparano et al ., 2008), and ovarian cancers (Suh et al ., 2013). Clinical use of paclitaxel is limited by adverse effects that include emesis, alopecia, and diarrhea, but these effects typically resolve with cessation of treatment (Reeves et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It exerts a significant effect on a variety of solid tumors, especially breast cancer, advanced ovarian cancer, non-small cell lung cancer, and Kaposi's sarcoma. [89][90][91] It has also been successfully used in nasopharyngeal cancer 92,93 and gastric cancer. 94,95 This study confirmed that paclitaxel inhibits the deacetylation of microtubules by EBV-miR-BART12, suggesting that paclitaxel may exert a significant inhibitory effect on nasopharyngeal and gastric cancer cells highly expressing EBV-miR-BART12.…”
Section: Discussionmentioning
confidence: 99%
“…However, bone marrow metastasis from NPC is rare, and the prognosis for these patients is exceedingly poor (8)(9)(10). Due to the severe complications associated with bone marrow metastasis, patients are typically ineligible for standard first-line regimens.…”
Section: Introductionmentioning
confidence: 99%